Penentuan Karakteristik Tanah Desa Ngasem dengan Metode ASTM - Safi'i, Annas Dwi; Candra, Agata Iwan; Altara, Jecksindio Elten; Oktaviadi, Mohammad Reza; Dwi K, Mohamad Agus; Mahardika, Rega; Aditia, Trio Syiwa (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2023)
Abstract: Soil is an important part of a sub-building structure, soil characteristics need to be considered in the initial planning of a construction, in order to achieve stability and security for the building above it. With different soil conditions, as is the case with the soil in Ngasem village which has low carrying capacity, it is necessary to know which structure meets the requirements for the soil conditions in Ngasem. To find out the characteristics of the soil is done by testing in the laboratory, namely testing the physical and mechanical properties. Testing the physical properties of the soil is testing the water content (Wc), specific gravity (Gs), Atterberg limits and soil unit weight (Î³). Mechanical testing with proctor test and direct shear strength. The method used is an experimental method by taking soil samples at a depth of ± 80 cm and conducting research tests in the Kadiri University laboratory. So that the results of soil classification with the SW-SM code are obtained which are classified as well-graded sandy soils with silt mixtures based on USCS and classified as (A-1-b) according to the AASHTO classification system. The Atterberg Limit of Low Plasticity (clay low plasticity) with a Plastic Index Value of 3.243 which is classified as Slightly Plastic, a shear angle value of 38.748° with a cohesion value of 1.914, a maximum dry unit weight value of 1.77 gr/cm3 , and an optimum moisture content of 14.44 . So that with this study, the community is expected to choose and adjust the type and quality of the structure of building materials in accordance with the state of the land. Keywords: Soil properties, Compaction, Shear Test, Liquid Limit, Plastic Limit